Effective arsenic removal using polyacrylonitrile-based ultrafiltration (UF) membrane - Lohokare, Harshada R.; Muthu, M. R.; Agarwal, Gopal P.; Kharul, Ulhas K. (Journal of Membrane Science, 2008)
Applicability of polyacrylonitrile (PAN)-based negatively charged ultrafiltration (UF) membrane for effective arsenic removal has been demonstrated, to our knowledge, for the first time. The hydrolysis of PAN-based UF membrane surface by NaOH leading to the formation of carboxylate (-COO-) groups and reduction in initial pore size rendered As-V rejection capability by Donnan exclusion principle. A lowering in pore size was indicated by the reduction in water flux and elevation in rejection of protein and polyethylene glycol (PEG). NaOH treatment leading to formation of carboxylate group on the membrane surface was indicated by FTIR-ATR, while contact angle measurement indicated increased hydrophilicity. This treatment rendered membrane surface smoothening as confirmed by SEM and AFM analyses. The molecular weight cut off after the NaOH treatment was found to be similar to 6 kDa. The rejection of pentavalent arsenic (As-V) by these surface modified membranes was studied with different feed concentration, cross-flow velocity, pressure, temperature and pH. Experiments with 50 ppb As-V in feed showed that arsenic rejection was close to 100% and remained constant up to 6 h. Feed sample concentration of 1000 ppb and 50 ppm of As-V showed >95% rejection at pH 7 and room temperature, but for 1000 ppm feed concentration, the rejection was 40-65%. For concentrations <= 50 ppm of arsenic in the feed, the rejection coefficient was not dependent on cross-flow velocity or transmembrame pressure. The rejection for 1000 ppm. concentration of As-V varied from 40 to 65% with variation in the cross-flow velocity and transmembrane pressure as the concentration polarization was important. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; concentration polarization; cross-flow velocity; Polyacrylonitrile; surface modification; Ultrafiltration